(untitled) (Bangladesh Journal of Medicine, 2013)
A description is given of a case of a young girl who presented with repeated episodes of pneumonia since childhood. In addition, she had episodes of intermittent diarrhoea. Her investigative work-up revealed a deficiency of serum immunoglobulins. The profile was suggestive of common variable immunodeficiency. Because of a relative rarity of this disease, it is often misdiagnosed earlier. Late diagnosis and delayed institution of immunoglobulin replacement therapy results in increased morbidity with a wide variety of organ-specific complications and increased mortality. DOI: http://dx.doi.org/10.3329/bjmed.v22i1.13597 Bangladesh J Medicine 2011; 22: 24-26